Judging architectural value - Saunders, William S. (Harvard design magazine readers, 2007)
Learning from St. Louis : the Arch, the Canon, and Bourdieu / Hélène Lipstadt -- What goes unnoticed : on the canonical quality of the PSFS Building / David Leatherbarrow -- Canon and anti-canon : on the fall and rise of the A + A / Timothy M. Rohan -- Canons in cross fire : on the importance of critical modernism / Charles Jencks -- In the shadow of a giant : on the consequences of canonization / Daniel Willis -- Eyesore or art? On Tyree Guyton’s Heidelberg project / John Beardsley -- Toward an architecture of humility : on the value of experience / Juhani Pallasmaa -- Why are some buildings more interesting than others? / Kurt W. Forster -- Questions of value : an interview with Kenneth Frampton / William S. Saunders and Nancy Levinson -- Most architecture should be modest : on architecture and aesthetic judgment / Roger Scruton -- From taste to judgment : multiple criteria in the evaluation of architecture / William S. Saunders -- Once again by the Pacific : returning to sea ranch / Tim Culvahouse and Lisa Findley -- The absence of presence : the Knickerbocker residence and the fate of nonelitist architecture / Diane Ghirardo.